Peran Pengolahan Udang Vaname Dalam Meningkatkan Ekonomi Masyarakat Desa Tambak Kalisogo - Adellia Mega Pratiwi; Dwindya Ililiyun; Muhammad Fiqih Samudera Wardhana; Wara Mustika (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Indonesia, which is known as a maritime country, of course has abundant marine resources. This diversity of marine natural resources not only provides extraordinary biodiversity, but also has significant economic potential for the country as a source of livelihood, food and income. So it is a very profitable step for Indonesia to continue processing marine resources including fish and shrimp.Â One real example of the potential of fisheries as a significant economic sector can be found in Tambak Kalisogo Village, which is one of the villages in Sidoarjo Regency where the majority of the population's livelihood is cultivating shrimp and processing vaname shrimp will have the potential to have a positive impact on the economy in Tambak Kalisogo Village. This research aims to find out the role of vaname shrimp processing in improving the economy of the Tambak Kalisogo Village community. The research method used in this research is the literature study method. According to Syaibani (2012), it is a method used by researchers to collect information that is relevant to the research topic being studied.